The Core Techniques of Morenian Psychodrama: A Systematic Review of Literature - Cruz, Ana; Sales, Célia M. D.; Alves, Paula; Moita, Gabriela (Frontiers in Psychology, 2018)
The original theory of psychodrama proposed by Moreno in 1921 has been adjusted and re-interpreted by several authors over the last three decades. This resulted in the proliferation of techniques whose definitions and contexts of application are unclear and poorly documented in the literature. The purpose of this review was three-fold: 1) to identify the psychodramatic techniques currently used for research and clinical purposes; 2) to extract and create a list of core techniques which are consensually used by psychodramatists, and which reflect the main principles of the Morenian theory of psychodrama; and 3) to propose an operationalised definition of the core psychodramatic techniques identified. To achieve this, a systematic review was conducted, according to the PRISMA guidelines (Moher, Liberati, Tetzlaff & Altman, 2009). The search was conducted between June - September of 2012 in the main electronic databases (e.g. PubMed, Embase, PsychINFO) and using the following keywords: “psychodrama”, “group psychotherapy”, “experiential psychotherapy”, “Moreno”, “intervention” and “techniques”. Fifty-six techniques were extracted from the 21 papers selected for review. Of these, a preliminary list of 30 techniques was selected, which was reduced to a total of 11 core techniques: role reversal, soliloquy, mirror, double, resistance interpolation, sculpture, social atom, intermediate objects, games, sociometry, role training. The credibility of this final core list was first checked with an expert in Morenian psychodrama, and later discussed with a network of 22 European psychodramatists to ensure full consensus. Overall, this review provides a contemporary framework for psychodramatists that reconciles the current approaches to psychodrama with the core techniques proposed by Moreno, and updates the definitions of these techniques, by merging the interpretations of different experts in the field. To have a list of core techniques which is consensually accepted from an international point of view is paramount not only for future research, but also for training purposes. The implications of this review for clinical practice are also discussed.